FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERHASILAN MAHASISWA TUNANETRA X DI IAIN IMAM BONJOL PADANG - Hartini Oktavia (Jurnal Penelitian Pendidikan Khusus, 2014)
Abstract : This study is about factors affecting the success of students with visual impairments X in IAIN Padang priest knurl. With the focus of the problem is internal and external factors that influence the success of students with visual impairments X in learning. This study used a qualitative descriptive method of data processing in the form of observations, interviews, and documentation. Keyword: Tunanetra ; keberhasilan belajar